2014
DOI: 10.2140/jomms.2014.9.313
|View full text |Cite
|
Sign up to set email alerts
|

Analytical solution for ductile and FRC plates on elastic ground loaded on a small circular area

Abstract: The problem of an infinite FRC slab resting on a Winkler-type elastic foundation and subject to a transversal load distributed over a small circular area is investigated in the present work. The mechanical behavior is described by the Kirchhoff theory of elastic-perfectly plastic plates obeying Johansen’s yield condition and associative flow rule. The governing equations within both the inner elastic-plastic circular region near to the loaded area and the outer elastic region are found in terms of the transver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
1
13
0
1
Order By: Relevance
“…Comparison between the results provided by the present study and that reported in[24] for n ? 0 and a/ L = 0.1…”
supporting
confidence: 68%
See 3 more Smart Citations
“…Comparison between the results provided by the present study and that reported in[24] for n ? 0 and a/ L = 0.1…”
supporting
confidence: 68%
“…n ? 0, then the results provided by Radi and Di Maida [24] are retrieved. Indeed, in that case, the foundation resembles a Winkler-type subgrade, and the corresponding values of the radii of the elastic and plastic regions and the ultimate carrying capacity are recovered (see Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the problem of an infinite elastic-plastic plate resting on an elastic Winkler-type subgrade and uniformly loaded on a circular area has been solved by Radi and Di Maida [2014] by assuming the Johansen yield criterion for the plate [Johansen 1962] and associative flow rule. In that work, the exact ultimate bearing capacity of the system has been assessed varying the radius of the loaded region.…”
Section: Introductionmentioning
confidence: 99%